Coordinated scan detection algorithm based on the global characteristics of time sequence. (2018) - Lv, Yanli; Li, Yuanlong; Xiang, Shuang; Xia, Chunhe
Scanning is a kind of activities or action for the purpose of acquiring the target host status information. In order to obtain the information more efficiently and more secretly, the attackers in the network often use coordinated scans to scan the target host or network. At present, there are no effective methods to detect the coordinated scan. We take scan sequences as time series and combine the general characteristics of time series. Then based on the features of time series clustering approach, we are going to find the coordinated scans governed by the same controller. Simulation and experiment results show that the methods we propose are better than the existing methods in accuracy and efficiency.